A STUDY ON RECTAL CARRIAGE OF MULTIRESISTANT GRAM-NEGATIVE BACILLI IN CHILDREN ATTENDING PEDIATRIC HOSPITAL AMBOHIMIANDRA, MADAGASCAR - Rakotoarisoa, Arinomenjanahary; Andriamandimbisoa, Herinjaka; Rasamiravaka, Tsiry; Andrianarivelo, Andry; Rasamindrakotroka, Andry (International Journal of Clinical and Biomedical Research, 2017)
Introduction: Gram-negative bacilli are often responsible for rectal colonization in children. These bacilli normally sensitive to third generation cephalosporins (3GC) have acquired disturbing antibiotic resistance in recent years, hence the interest of our study. The aims are to monitor the epidemiological evolution resistance of Enterobacteriaceae with antibiotics in particular β-lactams, estimate the prevalence of enterobacteria responsible for rectal colonization and their resistance to 3GC. Material and methods: This is a descriptive prospective study of Enterobacteriaceae in children attending Ambohimiandra Hospital for a period of 3 months (from 01 August to 31 October 2015). We have done a rectal swab of all the children whom we have parental consent. The samples were processed at the Laboratory of Medical Biology Faravohitra. The parameters studied are the antecedent of therapy antibiotic, notion of recent hospitalization and the results of microbiological examinations. Results: Of the 55 bacteriological samples obtained, 39 strains of Enterobacteriaceae were isolated, Escherichia coli (n = 12), Enterobacter cloacae (n = 13), Citrobacter spp (n = 1), Salmonella spp. (N = 5) and Shigella spp (n = 2), Proteus mirabilis (n = 1). Six isolated strains (50%) of Escherichia coli showed resistance to ceftriaxone, of which 4 (33.33%) produced ESBL. Conclusion: Gram-negative bacilli responsible for colonization of the digestive tract have several resistances to β-lactams, in particular 3GC, by the production of enzymes (Expanded spectrum beta-lactamase or ESBL and cephalosporinase or CASE) which hydrolyze these antibiotics. Measures to combat the spread of these phenomena resistance must be implemented in the Malagasy community to limit them. KEYWORDS: Rectal porous; Gram negative bacillus; ESBL; Multiresistence.